1996
DOI: 10.1002/(sici)1097-461x(1996)57:5<811::aid-qua1>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio dynamic polarizabilities of polymers. I. Hydrogen chain models

Abstract: mAb initio dynamic polarizabilities per unit cell of infinite stereoregular molecular hydrogen chains are calculated at the coupled Hartree -Fock level of approximation by using the random-phase approximation and the STO-3c and double-zeta atomic basis sets. Comparison with molecular calculations on increasingly large oligomeric chains emphasizes the nice extrapolation property of the polymeric technique that provides asymptotic values very close to the largest oligomeric values. The poles of the polarization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Conjugated polymers have large polarizabilities attributed to the delocalized nature of electronic excitations. Numerous experimental and theoreticalstudies have forged a pretty good understanding of their electronic and optical characteristics. , Pioneering theoretical investigations of NLO properties of polymers using solid-state physical concepts have been carried out by André, Champagne, and co-workers These investigations utilized the sum over states 273 and the polarization propagator technique. , A similar study has been done by using a variational method for the time-dependent wave function. , Ab initio approach combined CPHF method has been applied to polyene oligomers of moderate sizes, , extrapolated to the infinite systems using the periodic boundary conditions, , and extended into finite frequency off-resonant regime. It has been shown that vibrational contributions to the polarizability may be as important as their electronic counterparts. These nuclear effects arise from geometry deformations induced by the external field π-electron delocalization and polymer nonrigid energy potential surface strongly enhances the vibrational contribution.…”
Section: Quantum Confinement and Size Scaling Of Off-resonant Polariz...mentioning
confidence: 99%
See 2 more Smart Citations
“…Conjugated polymers have large polarizabilities attributed to the delocalized nature of electronic excitations. Numerous experimental and theoreticalstudies have forged a pretty good understanding of their electronic and optical characteristics. , Pioneering theoretical investigations of NLO properties of polymers using solid-state physical concepts have been carried out by André, Champagne, and co-workers These investigations utilized the sum over states 273 and the polarization propagator technique. , A similar study has been done by using a variational method for the time-dependent wave function. , Ab initio approach combined CPHF method has been applied to polyene oligomers of moderate sizes, , extrapolated to the infinite systems using the periodic boundary conditions, , and extended into finite frequency off-resonant regime. It has been shown that vibrational contributions to the polarizability may be as important as their electronic counterparts. These nuclear effects arise from geometry deformations induced by the external field π-electron delocalization and polymer nonrigid energy potential surface strongly enhances the vibrational contribution.…”
Section: Quantum Confinement and Size Scaling Of Off-resonant Polariz...mentioning
confidence: 99%
“…Numerous experimental and theoretical studies have forged a pretty good understanding of their electronic and optical characteristics. 15,31 Pioneering theoretical investigations of NLO properties of polymers using solid-state physical concepts have been carried out by Andre ´, Champagne, and coworkers [272][273][274][275][276] These investigations utilized the sum over states 273 and the polarization propagator technique. 274,276 A similar study has been done by using a variational method for the time-dependent wave function.…”
Section: Quantum Confinement and Size Scaling Of Off-resonant Polariz...mentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25][26][27] Without claiming to give a complete list of references we mention here the use of the summation over states procedure, 23 which corresponds to the UCHF-level, and the more rigorous approach based on the polarization propagator technique, 24,26 where in the randomphase approximation the reorganization of the electron distribution in the presence of the electric field is taken into account.…”
Section: Introductionmentioning
confidence: 99%